The Effectiveness of Ethanol Extract of Gamal Leaves (Gliricidia sepium) on Ascaridia galli Mortality in Vitro - Sandy, Berliana Dwi Nandita; Suprihati, Endang; Yudhana, Aditya; Hastutiek, Poedji; Wibawati, Prima Ayu; Praja, Ratih Novita (Jurnal Medik Veteriner, 2023)
This study aimed to determine the anthelmintic activity of the ethanol extract of gamal leaves (Gliricidia sepium) against Ascaridia galli in vitro. There were six treatment groups and each consisted of four replicates. This study used ten A. galli in each treatment for all replications. Observation and recording of death of A. galli was carried out at the 2nd, 4th, 6th, 8th, 10th and 12th hours. Death of A. galli was declared if there was no movement when clamped with anatomical tweezers. The data obtained were analyzed using the ANOVA test and continued with Duncan's test. The results showed that the ethanol extract of gamal leaves had an anthelmintic effect on A. galli worms in vitro. The extract with a concentration of 5% has almost the same anthelmintic properties as piperazine citrate 10 mg/ml. In conclusion, the higher the concentration of the extract, the higher the anthelmintic properties.